Model Tradisi Adat “Tepung Tawar” Dalam Penyelesaian Konflik Pengelolaan Sumber Daya Alam - Junaidi, Junaidi (Universitas Jambi, Fakultas Hukum, 2024)
The numerous disputes over the exploitation of natural resources mark this condition. Conflict resolution without going through the judicial route by utilizing the customary system has been passed down through generations in the life of customary law communities in Indonesia. The way to resolve conflicts based on Indonesian customary traditions aligns with values of justice that are prioritized over legal certainty. Conflict resolution through a familial approach is called